A Study on the efficiency of organic activator application to process refractory hard-to-beneficiate raw materials - Kenzhalievich, Kenzhaliyev Bagdaulet; Kairgeldyevna, Koizhanova Aigul; Rasimovich, Magomedov David; Beisenbekovna, Yerdenova Mariya; Nurdildakyzy, Bakrayeva Akbota; Mamanovich, Smailov Kenzhegali; Nurlanovich, Abdyldayev Nurgali (Jurnal Pendidikan Teknologi Kejuruan, 2024)
Polymetallic ores with complex mineralogical compositions pose significant challenges in flotation beneficiation, often resulting in suboptimal separation and recovery of valuable minerals. This study aims to analyse the effectiveness of alkyl benzene sulfonic acid (ABSA) as a frothing activator in improving the flotation performance and mineral recovery of polymetallic ore. It presents the results of flotation beneficiation experiments for polymetallic ore of complex mineralogical composition. Experiments were conducted on polymetallic ore samples using ABSA as the frothing activator in the flotation process. The performance was evaluated based on recovery rates and separation efficiency, comparing the results with standard floating frothing agents. The findings showed the highest efficiency of ABSA application for samples of mixed-type ores in increasing the recovery of gold, copper, zinc and lead in the collective concentrates of flotation beneficiation. ABSA activator promotes additional cleaning of fragments containing valuable metals from oxide films and coatings and the transfer of valuable metals' microparticles due to the organics' adsorption properties and the formation of metal-carbon bonds. Another effect of using this reagent is there was an increase in concentrate mass yield while maintaining the quality parameters. A similar effect was observed for beneficiation of copper ore with complex composition - copper recovery in the main concentrate increased. Selective flotation with the development of gold concentrate from hard-to-beneficiate polymetallic ore also showed a significant increase in gold recovery with ABSA pretreatment.